2018
DOI: 10.4103/ijnmr.ijnmr_208_17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of training on knowledge, perception and risk reduction regarding infection control among nurses in selected teaching hospitals in Nigeria

Abstract: Background:Healthcare workers, especially nurses, are at a high risk of infection. By complying with infection control measures, a lot of infections can be prevented. This study examined the effects of a training program on knowledge, perception, and risk reduction regarding infection control among nurses.Materials and Methods:This study adopted a pretest–posttest quasi-experimental design. The samples consisted of 87 participants comprising 42 nurses in the experimental group and 45 nurses in the control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
3
5
0
Order By: Relevance
“…Subsequently, the knowledge of nurses increased (38%) significantly after the training, indicating that the training had a positive effect on nurses' knowledge about HAI prevention. This result supports the findings by Farotimi et al (2018), Burute et al (2014), Adly et al (2014), and Taha (2014) that a training program is effective and nurses should be exposed to infection control to equip them with the necessary knowledge and skills to fight against the spread of infection in healthcare settings. Therefore, it is hoped that their behavior in preventing infection can be improved using the knowledge managementbased nursing care strategy.…”
Section: Discussionsupporting
confidence: 89%
“…Subsequently, the knowledge of nurses increased (38%) significantly after the training, indicating that the training had a positive effect on nurses' knowledge about HAI prevention. This result supports the findings by Farotimi et al (2018), Burute et al (2014), Adly et al (2014), and Taha (2014) that a training program is effective and nurses should be exposed to infection control to equip them with the necessary knowledge and skills to fight against the spread of infection in healthcare settings. Therefore, it is hoped that their behavior in preventing infection can be improved using the knowledge managementbased nursing care strategy.…”
Section: Discussionsupporting
confidence: 89%
“…A positive outcome is also seen for the participants' hand hygiene knowledge, where a significant increase in post-intervention mean score was obtained (p=0.000). All these results are in line with the study results from several other countries, where similar HAIs prevention education sessions were given to the HCWs and showed positive outcomes postintervention [13], [15], [19], [27].…”
Section: Discussionsupporting
confidence: 90%
“…In low-and middle-income countries (LMICs), basic hygiene standards are often lacking [1]. It has been reported that the HCWs in LMICs often have understood the knowledge of HAIs well [13]- [15], but the executions remain poor due to low compliance [16]- [18]. On the other hand, in high-income countries, awareness and conformity to standard guidelines have been well established [19]- [21].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Alhumaid et al’s 20 systematic review identified satisfactory knowledge levels encompassing standard precautions, hand hygiene, and disease-specific infection prevention and control measures. The demonstrated knowledge underscores the effectiveness of training programs provided to nurses in the emergency department, which is consistent with Farotimi et al, 21 highlighting the positive impact of continuous education on nurses’ adherence to infection prevention protocols.…”
Section: Discussionsupporting
confidence: 85%